Biological toxicity effects of florfenicol on antioxidant, immunity and intestinal flora of zebrafish (Danio rerio) - Xiao Yun; Jie Zhou; Jiting Wang; Qi Li; Yanji Wang; Wenjing Zhang; Zhicheng Fan (Ecotoxicology and Environmental Safety, 2023)
The accumulation of antibiotics in the aquatic environment is increasingly becoming a risk to the health of aquatic animal. The purpose of this study was to investigate the acute and chronic toxicity of florfenicol (FF) to zebrafish. A 56-day chronic toxicity test followed a 96-h acute toxicity test. The chronic toxicity test was divided into five FF concentration groups: 0 mg/L (C), 5 mg/L (T5), 10 mg/L (T10), 20 mg/L (T20) and 40 mg/L (T40). Each group had five replicates, with 20 Zebrafish per replicate. The acute toxicity test results showed that the 96 h-LC50 of FF was greater than 2000 mg/L, indicating low toxicity. The exposure concentrations of FF exceeding 20 mg/L can cause oxidative damage to the liver and gill tissues of fish, leading to the accumulation of oxidative products in the tissues and severe damage to antioxidant capacity. The reactive oxygen species (ROS) generated by severe oxidative stress activates the toll like receptors (TLR) pathway, inducing inflammation in the liver and gill tissues, stimulating the upregulation of inflammatory factor expression levels, and leading to immune system disorders. FF exposure at a concentration of 5 mg/L can lead to a significant decrease in the diversity and evenness of gut microbiota. The concentration of FF in water bodies above 37.52 mg/L poses a potential risk to aquatic products.